Biomechanical effect of ultraviolet-A-riboflavin cross-linking on simulated human corneal stroma model and its correlation with changes in corneal stromal microstructure. (August 2020) - Li, Hongxun; Liu, Taiwei; Mu, Bokun; Zhao, Xinheng; Xue, Chao; Shen, Min; Jhanji, Vishal; Wang, Yan
Abstract: In this study, we established an experimental human corneal stroma model of simulated cornea tissue composed of thin anterior cornea strips layers obtained from small incision lenticular extraction (SMILE) surgery. We investigated the biomechanical effect of ultraviolet-A- riboflavin cross-linking at different depths of corneal stroma model and correlated it with stromal microstructural changes examined by transmission electron microscopy (TEM). Corneal strips were harvested from fresh human corneal lenticules obtained after SMILE surgery. Experimental models (n = 34) were established by superimposing the corneal lenticule strips until their thickness reached close to 500 μm. Corneal cross-linking (CXL) was performed subsequently using standard or accelerated protocol. Elasticity and viscosity were quantified using stress-strain extensometer. TEM was used to visualize the collagen fiber diameter and interfibrillar spacing. The relative change in Young's modulus (rel. ΔE) decreased nonlinearly with increasing stromal depth both in the standard and accelerated groups. Compared to the sham controls, the rel. ΔE in standard and accelerated CXL groups increased significantly in the anterior 400 μm and 275 μm depth, respectively. Also, the relative change in stress (rel. ΔS) was significantly lower after standard and accelerated CXL compared to sham controls. Depth analysis showed similar results for the elastic effect. TEM images showed a small, non-significant increase in fibril diameter. The interfibrillar spacing decreased significantly after standard and accelerated CXL in the anterior-mid stromal region. We noted that the increase of corneal stiffness correlated with decrease in interfibrillar spacing after CXL. The stiffening effect was depth dependent. The effect of accelerated CXL was less in the deep corneal stromal regions compared to standard CXL. Highlights: Biomechanical property changes are based on corresponding changes in morphology. The increase of corneal stiffness correlated with decrease in interfibrillar spacing. The stiffening effect was depth dependent after Collagen crosslinking.